Use of anabolic-androgenic steroids and other substances prior to and during imprisonment - Results from the Norwegian Offender Mental Health and Addiction (NorMA) study. (1st December 2020) - Havnes, Ingrid Amalia; Bukten, Anne; Rognli, Eline Borger; Muller, Ashley Elizabeth
Highlights: Lifetime AAS use was reported by 30.0% of male and 6.4% of female prisoners. AAS users had earlier debuts and use of more drug types than non-AAS substance users. Among 1499 prisoners, 120 (8%) used AAS during the six months prior to incarceration. 110 of the 120 participants ceased use at current incarceration. Inmates with AAS withdrawal symptoms after incarceration may need tailored treatment. Abstract: Background: Anabolic-androgenic steroid (AAS) use is associated with health problems and substance use. Substance use is common among inmates. This study aims to estimate lifetime and prison use of AAS and other substances, compare characteristics of groups of inmates, and describe factors associated with AAS use in a national prison population. Methods: Data from the Norwegian Offender Mental Health and Addiction (NorMA) Study, a cross-sectional survey of people in prisons, included sociodemographic variables and lifetime and prison use of AAS and other substances. Altogether 1, 499 inmates, including 96 (6.4%) women, were divided into three mutually exclusive groups according to lifetime AAS use, non-AAS substance use and no substance use. Results: Lifetime AAS use was reported by 427 (28.5%) inmates; 6 women and 421 men. Non-AAS substance use was reported by 593 (39.6%) and 479 (31.9%) had never used AAS or non-AAS substances. Compared to the non-AAS substance group, the AAS group reported younger debut ages for nearly all non-AAS substances, higher mean number of non-AAS substances used in their lifetime (8.9, 6.6, p < 0.001), during the six months prior to incarceration (5.2, 3.1, p < 0.001), and during (2.3, 1.3, p < 0.001) imprisonment. Although 120 (8.0%) inmates used AAS during the six months prior to incarceration, only ten continued during imprisonment. Conclusions: Lifetime AAS use is common among inmates and may be an indicator of more severe substance use problems. Screening for previous and present AAS use at incarceration and increased staff awareness are needed to tailor treatment approaches appropriately.